Stylistic Study in Novel Negeri di Ujung Tanduk by Tere Liye: Its Influence on Character Education and Organizational Culture - Dessy Wardiah Hetilaniar (Proceeding International Conference on Digital Education and Social Science, 2024)
Study This aiming For describe forms stylistics in the novel The Land on the Edge of the Horn Tere Liye's work and identify its influence to education character as well as culture organization . Background study This due to the low level of knowledge and appreciation public to literary works , as well as difficulty participant educate in understand style Language in the learning process teaching . The method used in study This is method descriptive with technique data collection through demonstration For analyze novel content . Research results show that there is two form stylistics main in this novel , namely (1) language figurative , which is technique disclosure language whose meaning No direct nature literally , and (2) means rhetoric , which is used For to obtain effect specific to the reader . Research This expected can add insight and understanding participant educate as well as public about stylistics in literature. Implications from study This give impact positive to education character , because through style Language in the novel, participants educate can catch important moral values . In addition , the results study this also has potential enrich culture organization , especially in matter effective and constructive communication​ climate positive organization.​